Gluten-related nutritional challenges in pediatric subjects: treatment and beyond - Capra, Maria Elena; Sguerso, Tullia; Aliverti, Valentina; Pisseri, Gianlorenzo; Bellani, Arianna Maria; Berzieri, Martina; Montani, Anna Giuseppina; Esposito, Susanna; Biasucci, Giacomo (Frontiers in Nutrition, 2025)
Growing awareness of gluten-related disorders has led to a rising number of diagnoses of celiac disease (CD) and increasing adoption of the gluten-free diet (GFD), often without medical necessity. This narrative review summarizes current evidence on the main gluten-related conditions—CD, wheat allergy (WA), and non-celiac gluten sensitivity (NCGS)—and their nutritional implications, with particular focus on pediatric populations. Although these disorders share overlapping clinical features, they differ in pathogenesis, diagnostic criteria, and management. In CD, strict lifelong gluten exclusion remains essential for intestinal healing and symptom resolution, whereas in WA, wheat avoidance is the cornerstone of therapy. NCGS is characterized by gluten-related gastrointestinal and extra-intestinal symptoms in the absence of CD or WA, with notable clinical overlap with irritable bowel syndrome. Across all conditions, adherence to a GFD can lead to nutritional imbalances, including deficiencies in iron, folate, vitamin B12, vitamin D, calcium, zinc, and magnesium, as well as reduced fiber intake and unfavorable changes in gut microbiota. Overreliance on processed gluten-free foods may further increase cardiometabolic risks. In children, unmonitored GFDs may impair growth and neurodevelopment. Clinicians should ensure accurate differential diagnosis, provide nutritional counseling, and monitor long-term outcomes to balance the therapeutic benefits of GFD with potential risks.